1927 (vol II) Fla. Laws 212, pts. 18 - (:unkn) unknown (General Publisher, 1927)
Granted the city council the authority to prohibit and regulate the carrying of dirks, metal knuckles, or other dangerous weapons which are not firearms
--
Keywords: CARRY - NON-GUN ARMS